2017
DOI: 10.3389/fnagi.2017.00205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Strength Training and Anabolic Steroid in the Peripheral Nerve and Skeletal Muscle Morphology of Aged Rats

Abstract: Thirty male 20-month-old Wistar rats were divided into groups: IC—initial control (n = 6), FC—final control (n = 6), AC—anabolic hormone control (n = 6), ST—strength trained (n = 6) and STA—strength trained with anabolic hormone (n = 6). All groups were submitted to adaptation, familiarization and maximum load carrying test (MLCT). Strength training (6–8×/session with loads of 50%–100% MLCT, 3×/week and pause of 120 s) was performed in ladder climbing (LC) for 15 weeks. The administration of testosterone propi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 80 publications
(112 reference statements)
2
10
0
Order By: Relevance
“…We also found that the LT in the plantaris muscle had a more significant hypertrophy in Type II fibers, which corroborates the results of Krause Neto et al (2017) in a vertical ladder model that describe muscle hypertrophy with an associated higher contraction force generation capacity due to the increase in contractile proteins. This was also described in a review by Hawley et al (2014) that promoted adaptations in Type II fibers with increased oxidative profile, and both fiber types cause hypertrophy and maximal tension output.…”
Section: Discussionsupporting
confidence: 92%
“…We also found that the LT in the plantaris muscle had a more significant hypertrophy in Type II fibers, which corroborates the results of Krause Neto et al (2017) in a vertical ladder model that describe muscle hypertrophy with an associated higher contraction force generation capacity due to the increase in contractile proteins. This was also described in a review by Hawley et al (2014) that promoted adaptations in Type II fibers with increased oxidative profile, and both fiber types cause hypertrophy and maximal tension output.…”
Section: Discussionsupporting
confidence: 92%
“…After selection of the fields in the semi-thin sections, the ultra-thin sections were obtained with a diamond knife, in ultramicrotome (Sorvall MT-2), and contrasted with uranyl acetate and lead citrate, finally being analyzed by the transmission electron microscope. The techniques employed here, were in agreement with other publications done by our research group (Pianca et al, 2015 ; Carbone et al, 2017 ; Krause Neto et al, 2017b ).…”
Section: Methodssupporting
confidence: 90%
“…After an incision, a fragment of ~0.5 cm in length from the tibial nerve was removed from the posterior portion of the right leg. Then, we fixed the nerve fragment in 2.5% glutaraldehyde solution in phosphate buffer (0.2 M, pH 7.3) for 3 h (Pianca et al, 2015 ; Carbone et al, 2017 ; Krause Neto et al, 2017b ). Subsequently, we washed the material three times with the same buffer solution for 5 min at a time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Testosterone is a major male hormone applied in clinical practice in elderly men and patients with severe burns and other weaknesses to improve muscle function and quality of life [5]. In animal experiments, testosterone improved the muscle function of paraplegia, limb fracture and castration [6,7]. In the clinical, testosterone was associated with metabolic syndrome [8].…”
Section: Introductionmentioning
confidence: 99%